This is what I need to Simplify: (18 - 2a)²

The lecturer briefly mentioned that (18 - 2a)² = 18 x 2a², but I think he made an error? I don't know how he got to that answer. Substituting a value for "a" afterwards shows that it's wrong.

This is what I've done, using what I thought were normal techniques, but again substituting values for "a" afterwards shows that it's wrong too:

(18 - 2a)²

= (18 - 2a)*(18 - 2a)

= 18(18 - 2a) - 2a(18 - 2a)

= 324 - 36a - 36a + 2a².

= 324 - 72a + 2a².

Any help appreciated.

Thanks